2002
DOI: 10.1191/0269215502cr513oa
|View full text |Cite
|
Sign up to set email alerts
|

A study to compare the reliability of composite finger flexion with goniometry for measurement of range of motion in the hand

Abstract: In this study involving a subject with normal joints, goniometry is more reliable than CFF when only one measurer is involved. However, CFF may be a useful alternative where multiple joint measures are required, or when goniometry is impracticable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 21 publications
3
87
0
1
Order By: Relevance
“…For radial/ulnar deviation the mean absolute difference between the two raters was 5.1 with a maximum absolute difference of 10.7 . In both cases, the mean absolute difference between the two raters is better than that defined in the literature for manual goniometry (between 7 and 9 ) which is considered in clinical practice to be the gold standard of joint angle measurement [24], [25].…”
Section: B Static Participant Trial-inter-rater Reliabilitymentioning
confidence: 71%
“…For radial/ulnar deviation the mean absolute difference between the two raters was 5.1 with a maximum absolute difference of 10.7 . In both cases, the mean absolute difference between the two raters is better than that defined in the literature for manual goniometry (between 7 and 9 ) which is considered in clinical practice to be the gold standard of joint angle measurement [24], [25].…”
Section: B Static Participant Trial-inter-rater Reliabilitymentioning
confidence: 71%
“…Following completion of the case report form, a physical assessment was performed in a standardised order and standardised positions. This included the measurement of joint deformity (MCP ulnar/radial deviation in maximum pronation, where ulnar deviation is recorded as a positive value) and active range of motion (wrist flexion and extension from the neutral position with a goniometer, 47 combined finger flexion according to Ellis and Bruton, 48 combined finger extension and thumb opposition according to Kapandji). 49 A modified swollen and tender joint count (22 joints of hand and wrist) 50 was taken, along with a test of upper limb dexterity (nine-hole peg test according to Mathiowetz et al).…”
Section: Discussionmentioning
confidence: 99%
“…Taking the ankle criterion as an example, the responses include, two (0°-2° of eversion), four (3°-5°), five (6°-10°) six (11°-15°), seven (>15°). This gives little margin for error when using a tool which is based on observer interpretation, and is impractical based on research which has shown that inter-rater goniometric measures fall within 7° to 9° of each other [31,32]. inherent error, as the values obtained will largely depend on the observer and method of assessment.…”
Section: Discussionmentioning
confidence: 99%